Integrated approach for stress based lifing of aero gas turbine blades - Abu, Abdullahi Obonyegba (Cranfield University, 2013)
In order to analyse the turbine blade life, the damage due to the combined thermal and mechanical loads should be adequately accounted for. This is more challenging when detailed component geometry is limited. Therefore, a compromise between the level of geometric detail and the complexity of the lifing method to be implemented would be necessary. This thesis therefore focuses on how the life assessment of aero engine turbine blades can be done, considering the balance between available design inputs and adequate level of fidelity. Accordingly, the thesis contributes to developing a generic turbine blade lifing method that is based on the engine thermodynamic cycle; as well as integrating critical design/technological factors and operational parameters that influence the aero engine blade life. To this end, thermo-mechanical fatigue was identified as the critical damage phenomenon driving the life of the turbine blade. The developed approach integrates software tools and numerical models created using the minimum design information typically available at the early design stages. Using finite element analysis of an idealised blade geometry, the approach captures relevant impacts of thermal gradients and thermal stresses that contribute to the Thermo-mechanical Fatigue damage on the gas turbine blade. The blade life is evaluated using the Neu/Sehitoglu Thermo-mechanical Fatigue model that considers damage accumulation due to fatigue, oxidation, and creep. The leading edge is examined as a critical part of the blade to estimate the damage severity for different design factors and operational parameters. The outputs of the research can be used to better understand how the environment and the operating conditions of the aircraft affect the blade life consumption and therefore what is the impact on the maintenance cost and the availability of the propulsion system. This research also finds that the environmental (oxidation) effect drives the blade life and the blade coolant side was the critical location. Furthermore, a parametric and sensitivity study of the Neu/Sehitoglu model parameters suggests that in addition to four previously reported parameters, the sensitivity of the phasing to oxidation damage would be critical to overall blade life.